Monostotic eosinophilic granuloma. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
A 6-year-old girl was first observed for the presence of a frontal swelling dating from 40 days. The physical examination showed in the right frontal region a hemispheric swelling of about 1.5 cm, covered by normal skin (Fig. 1). At palpation the swelling was not very painful, had hard consistency and was adherent to the bone layer, while the skin moved on it. The rX showed an osteolytic image, CT (Fig. 2, 3) and RM highlighted a mass of about 1.5 cm, infiltrating and replacing the bone and dura mater. The bone tumor was removed and a plastic piece of spongy bone (Tutobone ®) was inserted with a residual scar (inset in Fig. 1). The histological examination (Fig. 4) showed an infiltrate of large cells with kidney-shaped nucleus and cytoplasm with sharp borders intermingled with numerous eosinophils. The clinical and histological data led to the final diagnosis of monostotic eosinophilic granuloma.